ISOLASI DAN UJI ANTIRADIKAL BEBAS MINYAK ATSIRI PADA DAUN SIRIH (Piper betle Linn) SECARA SPEKTROSKOPI ULTRA VIOLET-TAMPAK - Adi Parwata, I M. Oka; Susanah Rita, Wiwik; Yoga, Raditya (Jurnal Kimia (Journal of Chemistry), 2012)
Isolation, identification and free radical activities testing of essential oil from Piper betle Linn were carried out. Around 13,0 mL (12, 37 gram) of yellow essential oil was obtained from 10,0 kg fresh leaves of Piper betle Linn. The oil was then partitioned with MeOH : H2O (7:3), n-hexane and chloroform. Free radical activities testing showed n-hexana fraction was the most active which can reduced 66,27 % of DPPH for 5 minutes and 89,13 % in 60 minutes. GC-MS analysis revealed that there were 27 peaks. Based on the data analysis there were only 9 compound, i.e. 4-metil(1-metiletil)-3-sikloheksen-1-ol, 1-metoksi-4(1-propenil) benzene, 4-(2-propenil)fenol/kavicol, 4-alilfenilacetate, Eugenol, Karyofilen, 3-alil-6-metoksifenilasetat, 4-alil-1,2- diasetoksibenzena dan dekahidro-4a-metil-1-metilen-7(1-metiletenil) naftalena. Based on peak’s intensity the oil were dominated by 4 compound i.e. 4-allyl phenyl acetate, 2 methoxy-4- (2 prophenil) fenol/eugenol, 3-allyl-6-methoxy phenyl acetate, 4-(2-prophenyl)-phenol / cavikol.
Keywords: free radical activities, leaves of Piper betle (Linn), essential oil, GC-MS analysis